Spherical porous carbon material as well as preparation method and application thereof

By preparing spherical porous carbon materials, the problem of limited performance of existing porous carbon materials is solved, and higher mechanical properties and reaction properties are achieved, improving its performance in various applications.

CN119774607APending Publication Date: 2025-04-08SHANGHAI SHANSHAN NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411984917.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing porous carbon materials have limited performance in catalysis, adsorption, sensing, electrochemistry and other applications, and the improvement process is complex and difficult to control.

Method used

Using the preparation method of spherical porous carbon materials, an oil-in-water emulsion is formed by forming a styrene and divinylbenzene in the presence of an initiator and a dispersant, and a PS microsphere is prepared by polymerization, followed by oxidation, carbonization and activation treatment to form a spherical porous carbon material with high specific surface area and porosity.

Benefits of technology

It improves the mechanical properties, compressive strength and reaction properties of porous carbon materials, and enhances its application value in catalysis, electrochemistry and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774607A_ABST
    Figure CN119774607A_ABST
Patent Text Reader

Abstract

The invention discloses a spherical porous carbon material as well as a preparation method and application thereof, and belongs to the technical field of materials. The preparation method comprises the following steps: S1, dispersing styrene and divinylbenzene in the presence of an initiator and a dispersant to form an oil-in-water emulsion, and carrying out a polymerization reaction to prepare PS microspheres; s2, carrying out oxidation treatment and / or carbonization treatment on the PS microspheres at a high temperature; and S3, activating the PS microspheres treated in the previous step in an activating atmosphere at a high temperature to obtain the spherical porous carbon material. The porous carbon material prepared by the method is in a uniform spherical shape, can bear larger pressure and is firmer in structure, so that the material has higher compressive strength, the mechanical property of the porous carbon material is improved, the porous carbon material has higher specific surface area and higher porosity, and the performance of the spherical porous carbon material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, and in particular to a spherical porous carbon material and a preparation method and application thereof. Background Art

[0002] Porous carbon materials have many advantages such as high specific surface area, large pore volume, interconnected and uniform pores, and adjustable pore size, which make them widely used in catalysis, adsorption, sensing, electrochemistry, etc. In order to further improve the application of porous carbon materials in these aspects, heteroatoms (such as N, B, S, etc.) or heteroatom-containing groups (amino, nitro, sulfonic acid, etc.) are usually doped into the surface or structure of porous carbon materials to improve and enhance the performance of porous carbon materials. However, the improvement effect of the above materials is limited, and the process is complicated and difficult to control. Summary of the invention

[0003] In response to the above-mentioned problem of the current lack of high-performance porous carbon materials, the present invention provides a method for preparing spherical porous carbon materials. The porous carbon material prepared by this method is uniformly spherical, can withstand greater pressure, and has a more solid structure, so that the material has higher compressive strength, and the mechanical properties of the porous carbon material are improved. It also has a higher specific surface area and higher porosity, which further improves the performance of the spherical porous carbon material.

[0004] In one aspect, the present invention discloses a method for preparing a spherical porous carbon material, comprising the following steps:

[0005] S1: dispersing styrene and divinylbenzene in the presence of an initiator and a dispersant to form an oil-in-water emulsion, and performing a polymerization reaction to obtain PS microspheres;

[0006] S2: subjecting the PS microspheres to oxidation treatment and / or carbonization treatment at high temperature;

[0007] S3: activating the PS microspheres treated in the above steps at high temperature in an activation atmosphere to obtain the spherical porous carbon material;

[0008] In step S2, the temperature of the oxidation treatment is 150-400°C, and the temperature of the carbonization treatment is 400-600°C; in step S3, the temperature of the activation treatment is 800-1000°C.

[0009] The above preparation method first mixes the organic polymer raw materials, then mixes with the water phase, adds a dispersant, and disperses the monomer droplets more evenly in the water phase, promotes the formation of a spherical structure, and makes the microspheres of the oil phase wrapped by the water phase to form an oil-in-water structure. The dispersant forms a protective film on the surface of the monomer droplets, which reduces the interfacial tension between the droplets and the water phase, making it easier for the droplets to maintain a spherical shape. Then, at a certain temperature and time, the solid particles with a high degree of sphericity are PS microspheres. After oxidation and / or carbonization, an activation atmosphere is introduced for activation treatment to improve its reaction performance and obtain a high-performance spherical porous carbon material.

[0010] The spherical porous carbon material is spherical in shape. From the perspective of structural mechanics, the structure can withstand greater pressure and is more solid, so that the material has higher compressive strength, and the activation treatment can improve its reaction performance.

[0011] In some of the schemes, in the step S1, the mass ratio of styrene to divinylbenzene is 54±5.4:2.5, preferably 54:2.5.

[0012] In some of the schemes, in the step S1, the initiator is benzoyl peroxide; preferably, the mass ratio of styrene to divinylbenzene is 46±4.6:3.5, for example, 46:3.5.

[0013] In some of the schemes, the dispersant is polyvinyl alcohol; preferably, the mass ratio of styrene to polyvinyl alcohol is 46±4.6:1, for example, 46:1.

[0014] In some of the schemes, in the step S1, the polymerization reaction temperature is 70-90°C, preferably 85°C.

[0015] In some of the schemes, in the step S1, the polymerization reaction time is 5-12 hours, preferably 10 hours.

[0016] In some of the schemes, in the step S1, the dispersion method is homogenization; preferably, the homogenization condition is 10-20 m / s, for example, homogenization for 5-20 min under the condition of 15 m / s. It can be understood that the stirring and shearing action of the homogenizer can make the obtained emulsion droplet size smaller and more stable. The homogenization linear speed can be adjusted as needed, and 10-20 m / s is preferred.

[0017] In some of the schemes, in the step S1, the dispersant is added in the form of an aqueous solution; preferably, the concentration of the dispersant solution is 0.5-1.5wt%, preferably 1wt%.

[0018] In some of the schemes, in the step S1, after the initiator is added, it is stirred evenly at 40-60°C, preferably at 50°C.

[0019] In some of the schemes, in the step S1, after the reaction is completed, the reaction solution is filtered to obtain a filter cake, and the filter cake is dried and crushed to obtain PS microspheres; preferably, after the reaction is completed, the reaction solution is filtered to obtain a filter cake, the filter cake is rinsed with water 2-4 times the volume of the reaction solution, and the filter cake is dried in a vacuum drying oven at 110-130°C, crushed and passed through a 300-mesh sieve to obtain PS microspheres.

[0020] In some of the schemes, in the step S2, the PS microspheres are subjected to oxidation treatment and carbonization treatment in sequence.

[0021] In some of the schemes, in the S2 step, the gas source for the oxidation treatment is an oxygen-containing gas, such as air or oxygen.

[0022] In some of the schemes, in the step S2, the temperature of the oxidation treatment is 260°C.

[0023] In some of the schemes, in the S2 step, the gas source flow rate of the oxidation treatment is 1±0.5SLM (standard liters per minute), preferably 1SLM.

[0024] In some of the schemes, in the step S2, the oxidation treatment time is 1.5-3h, preferably 2h.

[0025] In some of the schemes, in the step S2, the atmosphere of the carbonization treatment is vacuum or inert gas, and the inert gas is preferably nitrogen.

[0026] In some of the schemes, in the step S2, the temperature of the carbonization treatment is 550°C.

[0027] In some of the schemes, in the step S2, the carbonization treatment time is 2-6 hours, preferably 3-5 hours, for example 4 hours.

[0028] In some of the schemes, in the step S3, the PS microsphere material obtained after the treatment in the previous steps is firstly depolymerized by rod grinding, and then activated; preferably, the rod grinding depolymerization method is mechanical grinding depolymerization, that is, the conventional rod grinding depolymerization method.

[0029] In some of the schemes, in the step S3, the temperature of the activation treatment is 850-950°C, preferably 900°C.

[0030] In some of the schemes, in the step S3, the activation treatment time is 2-10 hours, preferably 4 hours.

[0031] In some of the schemes, in the step S3, an inert gas is introduced to replace the reaction atmosphere, and then the activation atmosphere is introduced; preferably, the inert gas is argon or nitrogen.

[0032] In some of the schemes, in the S3 step, the activation atmosphere is CO and H2O vapor; preferably, the flow ratio of the CO and H2O vapor is 3-1:1, and more preferably 2:1.

[0033] In some of the schemes, in the step S3, the activation atmosphere is preheated to the same temperature as the activation treatment and then introduced into the reaction system.

[0034] In some of the schemes, in step S1, ferrocene is also added to participate in the polymerization reaction; preferably, the mass ratio of styrene to ferrocene is 54±5.4:1, more preferably 54:1.

[0035] In this scheme, since ferrocene is also added in the polymerization reaction, the obtained PS microspheres contain iron. When the activation atmosphere is introduced, the activation atmosphere of CO and water vapor can promote the activation of C, and carbon nanotubes are generated in the presence of iron atoms.

[0036] The spherical porous carbon material prepared by the above method has a higher specific surface area and higher porosity due to the presence of carbon nanotubes. Similarly, since the carbon nanotubes themselves have ultra-high compressive and tensile properties, the mechanical properties of the overall spherical structure are further improved. In terms of conductivity, the presence of carbon nanotubes in the spherical porous carbon gives it excellent ion channels, greatly increasing its conductivity.

[0037] In some of the solutions, the preparation method further comprises step S4, wherein the PS microspheres treated in the above steps are added to a hydrochloric acid solution for pickling. The pickling step can remove metal ions and expand the pores of the obtained carbon material.

[0038] In some of the above schemes, in the step S4, the concentration of the hydrochloric acid solution is 15-20wt%, for example, 18wt%.

[0039] In some of the above schemes, in the step S4, a post-treatment step is further included after the heating treatment, and the post-treatment step is: filtering the reaction solution to obtain a filter cake, washing the filter cake with water until it is neutral, and drying.

[0040] In some of the schemes, the preparation method further includes step S5, wherein step S5 is: reacting the spherical porous carbon material treated in the previous steps with a silicon hydride compound gas in a carrier gas atmosphere to perform silicon deposition treatment.

[0041] In some of the above schemes, in the step S5, the carrier gas atmosphere is nitrogen.

[0042] In some of the above schemes, in the step S5, the silicon hydride compound is Si n H 2n+2 , wherein n is a positive integer, for example, a positive integer of 1-4.

[0043] In some of the above schemes, in the step S5, the silicon hydride compound is selected from: one or two of monosilane and disilane, preferably monosilane.

[0044] In some of the above schemes, in the step S5, the reaction temperature is 400-500°C, preferably 480°C.

[0045] In some of the above schemes, in the step S5, the flow ratio of the carrier gas to the silicon hydride compound gas is 5 to 2:1, preferably 4:1.

[0046] In some of the above schemes, in the step S5, the time for the silicon deposition is 8-14 hours, preferably 10 hours.

[0047] In some of the schemes, the preparation method further includes step S6, wherein step S6 is: vapor-depositing carbon coating with an organic carbon source on the surface of the spherical porous carbon material treated in the above steps.

[0048] It is understandable that spherical porous carbon materials without vapor-deposited carbon coating can also be used as porous carbon materials, but in order to make the spherical porous carbon better used in lithium-ion battery negative electrode materials, it has been further improved, that is, silicon-carbon materials are obtained after silicon hydrogen compound vapor deposition.

[0049] In some of the above schemes, in the step S6, the organic carbon source is selected from: one or more of methane, acetylene and propane.

[0050] In some of the above schemes, in the step S6, the carbon content of the spherical porous carbon material treated with silicon deposition is 1 to 4%, preferably 3 to 4%.

[0051] In some of the above schemes, in the step S6, the thickness of the carbon layer deposited by the carbon coating is 1-100 nm, preferably 1-2 nm.

[0052] In some of the above schemes, in the step S6, the deposition temperature is 500-1000°C, preferably 600°C.

[0053] In some of the above schemes, in the step S6, the deposition time is 3 to 5 hours, preferably 4 hours.

[0054] On the other hand, the present invention also discloses the spherical porous carbon material prepared by the above preparation method.

[0055] In some embodiments, the D50 of the spherical porous carbon material is 5-15 μm, more preferably 10 μm.

[0056] On the other hand, the present invention also discloses the use of the above-mentioned spherical porous carbon material in preparing battery negative electrode materials.

[0057] Compared with the traditional doping method, the spherical porous carbon material obtained by the above method not only has a high specific surface area and excellent pore size and pore volume, but also has metallic conductivity and excellent compressive strength. It can be used as a negative electrode material for lithium-ion batteries and has higher mechanical properties and electrochemical energy.

[0058] In some embodiments, the battery is a lithium battery.

[0059] The above-mentioned lithium battery uses the above-mentioned spherical porous carbon material as the negative electrode material. Its excellent mechanical properties can well alleviate the volume expansion during the charging and discharging process in the lithium-ion battery, thereby improving the battery cycle stability. In addition, the carbon nanotubes in this material can greatly increase its conductivity, making it easier for lithium ions to be inserted and removed, and reducing the enrichment phenomenon during the ion transmission process, so that the battery's rate performance and safety performance are significantly improved.

[0060] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0061] The reagents and raw materials used in the present invention are commercially available.

[0062] The positive and progressive effects of the present invention are:

[0063] A method for preparing a spherical porous carbon material of the present invention, the obtained spherical porous carbon material is a porous carbon with high uniformity and spherical structure, and this structure can effectively increase the mechanical properties of the material and improve its mechanical strength. At the same time, the carbon nanotube structure can be catalytically generated in the spherical porous carbon, which not only further improves the mechanical strength of the material, but also increases the comparative area and pore volume of the material. At the same time, since the carbon nanotube itself has metallic conductivity, and it has the advantage of reducing the spacing of the gaps and accelerating the increase in the ion transfer rate. The above-mentioned spherical porous carbon material is especially used as a negative electrode material for lithium-ion batteries, which greatly improves the initial efficiency and capacity of the battery, and increases its cycle and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 This is a SEM image of the metal PS ball of Example 1 of the present application;

[0065] Figure 2 This is a SEM image of the spherical porous carbon material of Example 1 of the present application;

[0066] Figure 3 This is a particle size distribution diagram of the spherical porous carbon material of Example 1 of the present application. DETAILED DESCRIPTION

[0067] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0068] The reagents used in the following examples were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and ferrocene was purchased from Sinopharm Chemical Reagent Co., Ltd. Among them, the purity of styrene was 99.9%, the purity of divinylbenzene was 80%, the purity of ferrocene was 98%, the purity of BPO was 75%, and the purity of PVA was 98%.

[0069] Example 1

[0070] A spherical porous carbon material is prepared by the following method:

[0071] (1) Preparation of metallocene PS microspheres

[0072] Styrene, divinylbenzene and ferrocene were added in a mass ratio of 54:2.5:1, and stirred in a glass reactor for 30 minutes. Then, benzoyl peroxide (BPO) was added in a mass ratio of styrene to 46:3.5, and the mixture was heated to 50° C. and stirred for 30 minutes.

[0073] Then add the solution into a homogenizer, and then add a 1% polyvinyl alcohol (PVA) aqueous solution according to the mass ratio of styrene and polyvinyl alcohol (PVA) of 46:1. Stir for 10 minutes and then turn it off. Turn on the homogenizer for 5 minutes and then turn it off. Turn on the heating at 85°C and stir for 10 hours. Then filter the solution with a Buchner funnel, add pure water 3 times the volume of the solution, rinse 3 times respectively, and obtain a filter cake.

[0074] The filter cake was dried in a vacuum drying oven at 120°C for 12 hours. The dried material was crushed by a Chinese medicine grinder and passed through a 300-mesh sieve to obtain microspheres containing ferrocene, namely metallocene PS microspheres. The SEM image of the metallocene PS spheres is shown in Figure 1 shown.

[0075] (2) Oxidation

[0076] First, the dried PS microspheres containing ferrocene were placed in a rotary furnace with a rotation speed of 20 Hz, and the temperature was raised to 260°C at a rate of 0.5°C / min. Air was introduced with a flow rate of 1 SLM for 2 hours for oxidation treatment.

[0077] (3) Carbonization

[0078] After the oxidation treatment, the air was turned off and N2 was introduced for replacement for 1 hour, and then the temperature was increased to 550°C at 1°C / min and kept at this temperature for 4 hours for carbonization treatment.

[0079] (4) Activation

[0080] After the carbonization treatment, the material is depolymerized by rod grinding, and the depolymerized material is placed in a high-temperature activation furnace, first replaced by N2 for 1 hour, and then heated to 900°C at 5°C / min, and preheated CO and H2O vapor with a flow ratio of 2:1 is introduced for activation, and the preheating section temperature is also 900°C. After constant temperature activation for 4 hours, spherical porous carbon materials containing carbon nanotubes (CNTs) can be obtained.

[0081] (5) Pickling

[0082] The spherical porous carbon material containing CNTs is added to a diluted hydrochloric acid solution with a concentration of 18 wt %, so that the mass proportion of CNT spherical porous carbon is 15%. After filtering, it is washed with deionized water until it is neutral, and dried to obtain a material, which is a carbon nanotube spherical porous carbon material.

[0083] (6) Silicon deposition

[0084] The dried materials were placed in a fluidized bed and replaced with N2 for 1 hour. The temperature was raised to 480°C at 5°C / min, and then N2 and SiH4 preheated to 300°C with a flow ratio of 4:1 were introduced for silicon deposition. After 10 hours of deposition, the SiH4 gas was turned off.

[0085] (7) Vapor Deposition Carbon Coating

[0086] The temperature was raised to 600°C at a heating rate of 5°C / min, and C2H2 gas was introduced for 4 hours.

[0087] After the above treatment, the carbon nanotube spherical porous carbon material after silicon hydrogen compound vapor deposition is obtained, which can be used as a negative electrode material, such as Figure 2 As shown, the carbon content of the obtained product is 3-4wt% as measured by a high-frequency infrared carbon-sulfur analyzer, and the thickness of the carbon layer of the carbon-coated deposit is 1-2nm as measured by a transmission electron microscope.

[0088] The spherical porous carbon material of this embodiment is obtained by the polymerization reaction of styrene, divinylbenzene and metallocene to obtain metallocene PS balls. After washing and drying, it undergoes oxidation and carbonization processes to form nano-scale carbon balls. H2O vapor and CO are introduced at high temperature for activation and catalytic treatment. During this process, carbon nanotubes are gradually generated on the porous carbon balls. After acid washing, deionized water washing until neutral, and drying, carbon nanotube spherical porous carbon materials are obtained. After the spherical porous carbon material is subjected to silicon hydrogen compound vapor deposition, a silicon-carbon material is obtained, and after being coated with an organic carbon source, a porous carbon negative electrode active material for lithium-ion batteries can be obtained.

[0089] Example 2

[0090] A spherical porous carbon material is prepared by referring to the method of Example 1, except that in step (1), ferrocene is not added, and only styrene and divinylbenzene are fed for reaction.

[0091] Example 3

[0092] A spherical porous carbon material is prepared by referring to the method of Example 1, except that in step (4), the activation process temperature is 850°C.

[0093] Example 4

[0094] A spherical porous carbon material is prepared by referring to the method of Example 1, except that in step (4), the activation process temperature is 950°C.

[0095] Example 5

[0096] A spherical porous carbon material is prepared by referring to the method of Example 1, except that in step (4), the flow ratio of CO and H2O vapor is 3:1.

[0097] Example 6

[0098] A spherical porous carbon material is prepared by referring to the method of Example 1, except that in step (4), the flow ratio of CO and H2O vapor is 1:1.

[0099] Example 7

[0100] A spherical porous carbon material is prepared by referring to the method of Example 1, except that in step (5), the washing step with dilute hydrochloric acid having a concentration of 18 wt % is not performed.

[0101] Example 8

[0102] A spherical porous carbon material is prepared by referring to the method of Example 1, except that in step (2), no oxidation process is performed, that is, no air is introduced for heating reaction.

[0103] Example 9

[0104] A spherical porous carbon material is prepared by referring to the method of Example 1, except that in step (3), no carbonization process is performed, that is, no heating reaction is performed at 550°C.

[0105] Example 10

[0106] A spherical porous carbon material is prepared by referring to the method of Example 1, except that in step (4), the activated gas is not preheated, that is, the CO and H2O vapors introduced are not preheated but directly introduced for reaction.

[0107] Embodiment 11

[0108] A spherical porous carbon material is prepared by referring to the method of Example 1, except that in step (6), the silicon deposition SiH4 gas introduced is not preheated.

[0109] Effect experiment example

[0110] 1. Particle size test

[0111] The spherical porous carbon negative electrode active material prepared in Example 1 was taken and its particle size distribution was analyzed using a particle size analyzer (Malvern Panalytical 2000) according to conventional methods.

[0112] The results are as follows Figure 3 As shown, the unit of the horizontal axis in the figure is μm, and the results show that the particle size of the spherical porous carbon material is concentrated around 10 μm, and most of it is concentrated around 5-15 μm.

[0113] 2. Electrochemical performance test

[0114] The spherical porous carbon negative electrode active material prepared in each example and comparative example was coated on a copper foil, and vacuum dried and rolled according to a conventional method to prepare a negative electrode sheet.

[0115] A 1 mol / L LiPF6 three-component mixed solvent electrolyte with a volume ratio of ethyl carbonate: dimethyl carbonate: ethyl methyl carbonate = 1:1:1 was used, a polypropylene microporous membrane was used as a separator, and a metal lithium sheet was used as a positive electrode. The button cells were assembled in an inert gas glove box system filled with argon.

[0116] The button cell was charged and discharged on the battery test system at room temperature with a constant current of 0.1C and a charge and discharge voltage limit of 0.005 to 1.5V. Cycle stability is the ratio of the specific capacity to the initial specific capacity after 200 charge and discharge cycles under the same test conditions. The lower the value, the faster the capacity decreases and the worse the cycle stability. See the table below for specific data.

[0117] Table 1 Performance data of various button batteries

[0118]

[0119] The above-mentioned first-week specific capacity is the specific capacity ratio before 200 charge and discharge cycles, the first efficiency is the ratio of the charging capacity to the discharging capacity in the first cycle, and the capacity retention rate is the ratio of the specific capacity after 200 charge and discharge cycles to the initial specific capacity before the charging cycle, that is, the termination charging specific capacity / first-week charging specific capacity. The specific capacity is the amount of electricity obtained per unit mass or unit volume of active material.

[0120] From the above experimental results, it can be seen that the spherical porous carbon material prepared in the above embodiment maintains relatively stable electrochemical performance and has excellent electrochemical performance in capacity and cycle, which should be due to its good electrical conductivity.

[0121] The spherical porous carbon material prepared in Example 1 has a first-week capacity of up to 2018.3 mAh / g, a high first efficiency, and an optimal capacity retention rate. The main reason is that CO and H2 are produced during the activation process and the H2O vapor activation process. When CO meets nano-iron particles at high temperature, a disproportionate reaction will occur to generate CNTs. An appropriate amount of H2 will promote the disproportionate reaction in the direction of generating CNTs, resulting in a larger internal pore volume and a larger specific surface area. The amount of silicon that can be deposited increases, and the capacity is relatively improved. In addition, its chemical properties are mild, which improves the material's acid and oxidation resistance, reduces the consumption of active lithium during the charge and discharge process, and improves the first efficiency. It can also make the structure more solid, improve the mechanical strength, and buffer the volume expansion during the charge and discharge process. It also has better conductivity and better cycle performance.

[0122] The spherical porous carbon material prepared in Example 2 does not contain ferrocene, so that there are no iron nanoparticles in the porous carbon that can catalyze the generation of carbon nanotubes, resulting in a decrease in the structural performance and electrochemical performance of the material.

[0123] The spherical porous carbon material prepared in Example 3 has a low activation temperature, resulting in relatively small pore volume and comparative area, and less silicon deposition, resulting in low capacity and first efficiency, and is not conducive to the formation of CNTs, thereby reducing its cycle stability.

[0124] The spherical porous carbon material prepared in Example 4 has a high activation temperature, resulting in too many macropores and too few mesopores in the porous carbon, and the weak structural strength leads to a small amount of silicon deposition, which affects the electrochemical performance, resulting in reduced capacity and a significant decrease in cycle performance.

[0125] In the spherical porous carbon material prepared in Example 5, the CO and H2O vapor flow ratio during the activation process is too high, and the insufficient H2O vapor results in a poor activation effect. In addition, the H2 content generated during the H2O vapor activation process is low, and it is difficult to generate CNTs, which leads to a decrease in capacity and first coulombic efficiency, and the cycle will also deteriorate.

[0126] The spherical porous carbon material prepared in Example 6 has a too low CO and H2O vapor flow ratio during the activation process, insufficient CO, and too high a H2 content produced during the H2O vapor activation process, making it difficult to generate CNTs, resulting in reduced capacity and first coulombic efficiency, and poor cycle performance.

[0127] The spherical porous carbon material prepared in Example 7 is not washed with dilute hydrochloric acid. The presence of iron impurities inside the material will lead to a decrease in capacity. At the same time, the presence of magnetic foreign matter will cause edges or spikes to form inside the battery, which will significantly reduce its capacity and efficiency. Long-term presence will pierce the diaphragm and form a short circuit.

[0128] The spherical porous carbon material prepared in Example 8 does not undergo an oxidation process, resulting in uneven overall particle size, destroyed spherical structure, reduced mechanical strength, and uneven silicon deposition. Its initial capacity efficiency and capacity retention rate will be significantly reduced.

[0129] The spherical porous carbon material prepared in Example 9 does not undergo a carbonization process, resulting in excessive volatile matter and other impurities in the overall structure, affecting the activation process, making it difficult to generate CNTs, resulting in reduced mechanical strength, less silicon deposition, and most of the formation of surface floating silicon, which significantly reduces its initial efficiency and capacity retention rate.

[0130] For the spherical porous carbon materials obtained in Examples 10 and 11, the activation gas is introduced without preheating, resulting in a poor activation effect, hindered CNT generation, and a small amount of silicon deposition. The silicon deposition SiH4 gas is introduced without preheating, which also results in a small amount of silicon deposition, thereby reducing its capacity efficiency and capacity retention rate to a certain extent.

Claims

1. A method for preparing a spherical porous carbon material, characterized in that: The following steps are involved: S1: dispersing styrene and divinylbenzene in the presence of an initiator and a dispersant to form an oil-in-water emulsion, and performing a polymerization reaction to obtain PS microspheres; S2: subjecting the PS microspheres to oxidation treatment and / or carbonization treatment at high temperature; S3: activating the PS microspheres treated in the above steps at high temperature in an activation atmosphere to obtain the spherical porous carbon material; In step S2, the temperature of the oxidation treatment is 150-400°C, and the temperature of the carbonization treatment is 400-600°C; in step S3, the temperature of the activation treatment is 800-1000°C.

2. The preparation method according to claim 1, characterized in that Meet one or more of the following conditions: (1) In the step S1, the mass ratio of styrene to divinylbenzene is 54±5.4:2.5, preferably 54:2.5; (2) In the step S1, the initiator is benzoyl peroxide; preferably, the mass ratio of styrene to divinylbenzene is 46±4.6:3.5, for example, 46:3.5; (3) In the step S1, the dispersant is polyvinyl alcohol; preferably, the mass ratio of styrene to polyvinyl alcohol is 46±4.6:1, for example, 46:1; (4) In the step S1, the polymerization reaction temperature is 70-90°C, preferably 85°C; (5) In the step S1, the polymerization reaction time is 5-12 hours, preferably 10 hours; (6) In the step S1, the dispersion method is homogenization; preferably, the homogenization condition is 10-20 m / s, for example, homogenization for 5-20 min under the condition of 15 m / s; (7) In the step S1, the dispersant is added in the form of an aqueous solution; preferably, the concentration of the dispersant solution is 0.5-1.5 wt%, preferably 1 wt%; (8) In the step S1, after the initiator is added, stirring is performed uniformly at 40-60° C., preferably at 50° C.; (9) In the step S1, after the reaction is completed, the reaction solution is filtered to obtain a filter cake, and the filter cake is dried and crushed to obtain PS microspheres; Preferably, after the reaction is completed, the reaction solution is filtered to obtain a filter cake, the filter cake is washed with water 2-4 times the volume of the reaction solution, and then dried in a vacuum drying oven at 110-130° C., crushed and sieved through a 300-mesh sieve to obtain PS microspheres; (10) In the step S2, the PS microspheres are subjected to oxidation treatment and carbonization treatment in sequence; (11) In the step S2, the gas source for the oxidation treatment is an oxygen-containing gas, such as air or oxygen; (12) In the step S2, the temperature of the oxidation treatment is 260°C; (13) In the step S2, the gas source flow rate of the oxidation treatment is 1±0.5 SLM, preferably 1 SLM; (14) In the step S2, the oxidation treatment time is 1.5-3 h, preferably 2 h; (15) In the step S2, the atmosphere of the carbonization treatment is a vacuum or an inert gas, and the inert gas is preferably nitrogen; (16) In the step S2, the temperature of the carbonization treatment is 550°C; (17) In the step S2, the carbonization treatment time is 2-6 hours, preferably 3-5 hours, for example 4 hours; (18) In the step S3, the PS microsphere material obtained after the treatment in the above steps is firstly depolymerized by rod grinding, and then activated; preferably, the rod grinding depolymerization method is mechanical grinding depolymerization; (19) In the step S3, the temperature of the activation treatment is 850-950°C, preferably 900°C; (20) In the step S3, the activation treatment time is 2-10 h, preferably 4 h; (21) In the step S3, an inert gas is introduced to replace the reaction atmosphere, and then the activation atmosphere is introduced; preferably, the inert gas is argon or nitrogen; (22) In the step S3, the activation atmosphere is CO and H2O vapor; preferably, the flow ratio of CO and H2O vapor is 3-1:1, preferably 2:1; (23) In the step S3, the activation atmosphere is preheated to the same temperature as the activation treatment and then introduced into the reaction system.

3. The preparation method according to claim 1, characterized in that: In the step S1, ferrocene is also added to participate in the polymerization reaction; preferably, the mass ratio of styrene to ferrocene is 54±5.4:1, more preferably 54:

1.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The step S4 is further included, wherein the PS microspheres treated in the above steps are added into a hydrochloric acid solution for pickling.

5. The preparation method according to claim 4, characterized in that: Meet one or more of the following conditions: (1) In the step S4, the concentration of the hydrochloric acid solution is 15-20 wt%, for example, 18 wt%; (5) In the step S4, a post-treatment step is further included after the heating treatment, and the post-treatment step is: filtering the reaction solution to obtain a filter cake, washing the filter cake with water until it is neutral, and drying.

6. The preparation method according to claim 5, characterized in that: The method further comprises step S5, wherein the step S5 is: reacting the spherical porous carbon material treated in the above steps with silicon hydrogen compound gas in a carrier gas atmosphere to perform silicon deposition treatment.

7. The preparation method according to claim 6, characterized in that: Meet one or more of the following conditions: (1) In the step S5, the carrier gas atmosphere is nitrogen; (2) In the step S5, the silicon hydride compound is Si n H 2n+2 , wherein n is a positive integer, for example, a positive integer of 1-4; further, the silicon hydride compound is selected from: one or two of monosilane and disilane, preferably monosilane; (3) In the step S5, the reaction temperature is 400-500°C, preferably 480°C; (4) In the step S5, the flow ratio of the carrier gas to the silicon hydride compound gas is 5 to 2:1, preferably 4:1; (5) In the step S5, the silicon deposition time is 8-14 hours, preferably 10 hours.

8. The preparation method according to claim 6, characterized in that: The step S6 is further included, wherein the surface of the spherical porous carbon material treated in the above steps is subjected to vapor deposition carbon coating with an organic carbon source; Preferably, one or more of the following conditions are met: (1) In the step S6, the organic carbon source is selected from one or more of methane, acetylene and propane; (2) In the step S6, the carbon content of the spherical porous carbon material treated with silicon deposition is 1 to 4%, preferably 3 to 4%; (3) In the step S6, the thickness of the carbon layer deposited by the carbon coating is 1-100 nm, preferably 1-2 nm; (3) In the step S6, the deposition temperature is 500-1000° C., preferably 600° C.; (4) In the step S6, the deposition time is 3 to 5 hours, preferably 4 hours.

9. The spherical porous carbon material prepared by the preparation method according to any one of claims 1 to 8; preferably, the D50 of the spherical porous carbon material is 5 to 15 μm, more preferably 10 μm.

10. Use of the spherical porous carbon material according to claim 9 in preparing a negative electrode material for a battery, wherein the battery is a lithium battery.

Citation Information

Patent Citations

  • Preparation method of polystyrene resin-based spherical activated carbon

    CN113443625A

  • Lithium ion battery silicon-carbon negative electrode material and preparation method and application thereof

    CN119040844A

  • Carbon porous electrode and method for manufacturing the same

    JP2016027599A

Cited By

  • Catalytic particle-loaded carbon microspheres as well as preparation method and application thereof

    CN120790150A